REAKTUALISASI PENGUKURAN ARAH KIBLAT DENGAN METODE SEGITIGA BOLA PADA MASJID DAN MUSHOLLA - ANDI SUSANTO; Diana Nurfadilah; Siti Zaenab (KASBANA, 2021)
An understanding of the Qibla direction is very important for Muslims, because facing the Qibla is one of the legal requirements for performing prayers. Although now the technology to determine the Qibla direction is sophisticated, it is necessary to know how to determine the actual Qibla direction. The determination of the direction of the Qibla with the spherical triangle method is based on a triangle on the surface of the globe which is formed by three large circles of the globe, namely two circles of the earth's longitude and one circle of Qibla. The intersection of the three large circles forms three points, namely point A (Makkah), point B (the location where the Qibla direction will be calculated), and point C (the North Pole). The steps in determining the Qibla direction include: (1) Prepare the data needed in calculating the Qibla direction of a place, namely latitude and longitude data for the Kaaba (Makkah city), as well as latitude and longitude data for the location/city to be calculated. the qibla direction; (2) Calculation of the Qibla direction using the formula , with: B = Angle of the direction of the Qibla of a place, C = The difference between the longitude of the Kaaba and the longitude of the place where the Qibla direction is being sought, a = 90o – tp (latitude), and b = 90o – ka (Kaaba latitude); (3) Calculation of true Qibla azimuth from true north in a clockwise direction, where true Qibla azimuth = 360o – Qibla direction angle (B); (4) Determination of the actual Qibla direction by measuring using an arc ruler as large as true Qibla azimuth from true north.